Effect of Errors of Determination of Thermochemical and Thermophysical Characteristics of Insulating Materials on Integral Process Parameters of their Polymerization; Chemical and Petroleum Engineering; Vol. 51, iss. 3 - Ivanova E. V. Evgeniya Vladimirovna (2015, 2015)
Title screen